Chapter Le Lettere del beato Colombini come esempio di dialetto senese secondo Giovan Girolamo Carli - Bruttini, Elisa (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
Giovan Girolamo Carli, a Sienese scholar (1719-1786), focused on the language of the Letters, usually considered a secondary aspect compared to their historical and theological value. Probably pushed by an anonimous client, Carli was planning to publish the first critical edition of the Letters, strictly philological, supported by insights on the life of the Blessed and a dictionary. His manuscript drafts, even incomplete, are however a precious source for reconstructing the original documents tradition, since he directly consulted and compared different and authoritative copies. Carli's purpose was to celebrate a fellow citizen, but also to prove the Sienese linguistic primacy instead of the Florentine one - as in art historiography -, and propose an authentic style against the contemporary mediocrity.